Penerapan dan Manfaat Machine Learning di Rumah Sakit - Sodikin, Muh Ikbal (Multiverse: Open Multidisciplinary Journal, 2023)
Machine learning is a highly useful method for solving various problems, streamlining task execution, and making significant contributions in various fields, including the healthcare industry. For instance, within the realm of hospitals or healthcare, the use of machine learning enables doctors to swiftly diagnose heart diseases, reducing the time required for the diagnostic process. This technology also has the capability to learn autonomously without the need for continuous supervision. However, like any other technology, machine learning has its strengths and weaknesses. Strengths of machine learning include efficient problem-solving, rapid data analysis, and autonomous learning capabilities. However, weaknesses encompass susceptibility to biased training data, lack of interpretability in complex models, and potential challenges in handling unforeseen scenarios. Balancing these aspects is crucial for maximizing the benefits of machine learning across diverse applications.